The Effect Of Transformational Leadership, Workplace Incivility, and Job Anxiety On Innovative Work Behavior Employees Of Pt Madu Baru Madukismo - Dimas Rizky Huda Huda (Universitas Hamzanwadi, 2026)
This study aims to analyze the influence of Transformational Leadership, Workplace Incivility, and Job Anxiety on Employee Innovative Work Behavior at PT Madu Baru Madukismo. A causal descriptive quantitative approach was applied in this study through a survey method. Data collection was carried out by distributing a structured questionnaire to all employees totaling one hundred people using saturated sampling or census techniques. Furthermore, the primary data collected was analyzed using multiple linear regression analysis techniques. The results of the study show that Transformational Leadership has a positive and significant effect on Innovative Work Behavior. These findings confirm that inspirational and supportive leaders are effective in spurring employee courage in promoting and realizing creative ideas. On the other hand, Workplace Incivility was shown to have no significant effect on Innovative Work Behavior, which indicates that there is an internal adaptation mechanism for employees so that work incivility does not directly kill creativity. Meanwhile, the Job Anxiety variable uniquely showed a positive and significant influence on Innovative Work Behavior. This indicates that work anxiety to a certain extent acts as a functional trigger that encourages employees to proactively seek breakthrough solutions to mitigate task pressure. Implicitly, organizations are advised to combine strengthening transformational leadership with managing employee anxiety wisely to maintain the sustainability of innovation